Call-type dependence in multiskill call centers. (June 2013) - Jaoua, Amel; L'Ecuyer, Pierre; Delorme, Louis
The effect on multiskill call-center performance of pooling dependent call types is investigated. For this purpose, a copula-based modeling approach is used to provide multivariate models that take into account the call types' asymmetric dependence structures found in empirical data. Then, the realistic input models of the call-type-dependent arrival processes are used in a simulation study to explore the sensitivity of the pooling decision to this dependence. We find that the widely used assumption of independence, as well as the misspecification of the dependence structure, can lead to substantial misestimation of call-center performance. This demonstrates the importance of modeling call-type dependence in stochastic simulation studies of call centers. We also show, through case studies, that pooling two asymmetric left-tail-dependent call types is more likely to lead to low agents occupancy; whereas the presence of right-tail dependence structure increases the risk of service-level shortfall. This work provides new managerial insights to improve decision making in determining which call types to merge in the same pool in multiskill call centers.